PENERAPAN TEKNIK “APA” UNTUK MENINGKATKAN KEMAMPUAN TENAGA ADMINISTRASI SEKOLAH DALAM MENGGUNAKAN TIK - Abdul Hamid (Vidya Karya, 2019)
Abstract.  This school action research was intended to find out the  information about the application of the “APA” technique   to increase  the school administration staffs' ability in using Information and Communication Technologies (ICT)  at SMP Negeri 7 Banjarmasin. The subjects of this research consisted of 4 school administration staffs. This research was conducted in two cycles with the four steps: planning, acting, observing and reflecting. The quantitatif data of the competence achieved by the school administration staffs  was collected by scoring their works on each “Application Step” and also supported with the qualitatif data of the observation results collected through observation sheets. The result of this study showed that the application of the “APA technique was able to increase the school administration staffs’ability   in using Information and Communication Technologies (ICT) at SMP Negeri 7 Banjarmasin. Keywords: School administration staffs’ability,  Information and Communication Technologies (ICT), “APA” technique Abstrak. Penelitian tindakan sekolah ini bertujuan untuk  mendapatkan informasi tentang penerapan teknik "APA" dalam meningkatkan kemampuan tenaga administrasi sekolah dalam penggunaan TIK di SMP Negeri 7 Banjarmasin. Penelitian ini dilaksanakan di SMP Negeri 7 Banjarmasin dengan subjek penelitian sebanyak 4 orang tenaga administrasi. Penelitian ini dilaksanakan dengan 2 siklus dengan tahapan kegiatan mulai perencanaan, pelaksanaan, pengamatan/observasi dan refleksi. Data kuantitatif berupa  kemampuan tenaga administrasi sekolah dalam penggunaan TIK diperoleh dengan melakukan penskoran terhadap hasil kerja mereka pada tahap aplikasi dan didukung oleh data kualitatif dari hasil pengamatan yang dikumpulkan melalui lembar observasi. Hasil penelitian menunjukkan bahwa penerapan teknik "APA" dapat  meningkatkan kemampuan tenaga adminstrasi sekolah dalam pnggunaan TIK di SMP Negeri 7 Banjarmasin. Kata kunci:Kemampuan tenaga administarasi sekolah, TIK, teknik “APA”.